2008
DOI: 10.1590/s1678-58782008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Performance profiling of boric acid as lubricant in machining

Abstract: Turning is a widely used metal removal process in manufacturing industry that involves generation of high cutting forces and temperature. Lubrication becomes critical to minimize the effects of these forces and temperature on cutting tool and workpiece. The conventional cutting fluids employed in machining have certain limitations with regard to their use for ecological and economic reasons. Development of lubricants that are eco friendly is acquiring importance. In this context, application of solid lubricant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Therefore, there are boronic acid compounds in the structure of drugs used in medical fields such as oncology, virology, neurology and hematology [9][10][11]. It is used in many areas such as antiseptic solution in eyes and ears [12,13], insecticide in agriculture [14], lubricant on ceramic and metal surfaces [15], acne treatment and skin lotions [16] and liquid crystal display panel in industry [17]. The need for alternative new materials in all these areas is increasing day by day.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there are boronic acid compounds in the structure of drugs used in medical fields such as oncology, virology, neurology and hematology [9][10][11]. It is used in many areas such as antiseptic solution in eyes and ears [12,13], insecticide in agriculture [14], lubricant on ceramic and metal surfaces [15], acne treatment and skin lotions [16] and liquid crystal display panel in industry [17]. The need for alternative new materials in all these areas is increasing day by day.…”
Section: Introductionmentioning
confidence: 99%
“…Depending upon the characteristics of nanoparticles such as size, shape and concentration, the friction and wear between the two contacting surfaces were reduced [13]. The lubricating properties of boric acid (H 3 BO 3 ) were studied which was commercial available in the market and environmentally safe [14]. The environmental protection agency act established that boric acid does not cause any harm or pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Junbin tested the borate containing nitrogen with the ball on disk tribometer test and reported its good antiwear performance by forming borate ester and BN protective layers on the surface . Erdemir, Wei et al, and Damera et al reported that boric acid provided very low friction between an aluminum workpiece and a steel forming tool in metal forming applications . Kimura et al added BN into the base oil and tested with a ring on roller tribometer and reported that BN can be considered to be a potential lubricating oil additive for applications .…”
Section: Introductionmentioning
confidence: 99%
“…20 Erdemir, Wei et al, and Damera et al reported that boric acid provided very low friction between an aluminum workpiece and a steel forming tool in metal forming applications. [21][22][23] Kimura et al added BN into the base oil and tested with a ring on roller tribometer and reported that BN can be considered to be a potential lubricating oil additive for applications. 24 However, Demas et al compared wear and friction behavior of BN and MoS 2 nanoparticles, which was added to PAO 10 base oil.…”
Section: Introductionmentioning
confidence: 99%